Leveraging Future LEO Constellations for the Precise Orbit Determination of Lower Small Satellites - Allahvirdizadeh, Amir; El-Mowafy, Ahmed; Wang, K. (Institute of Navigation, 2024)
Low earth orbit (LEO) constellations offer possible significant augmentation to the Global Navigation Satellite Systems (GNSS) for positioning, navigation, and timing (PNT) applications. This study explores a new application of forthcoming LEO-PNT constellations; the utilization of signals from higher LEO satellites for precise orbit determination (POD) of lower satellites, such as CubeSats. The integration of LEO-based orbit determination with existing GNSS-based LEO POD methods introduces redundancy and resilience, critical for monitoring the increasingly crowded LEO region in the future. To explore this approach, a simulation is conducted using a constellation of 240 LEO satellites at 1000 km altitude, designed to provide global coverage for the POD of lower satellites. Actual onboard GNSS observations of a 3U CubeSat and its attitude information are employed in a reduced-dynamic POD, generating a true trajectory for the CubeSat. Simulated orbits for the entire constellation and the true trajectory of the CubeSat are used to simulate the navigation signals from the LEO constellation to the CubeSat. Various errors and biases are considered in the simulated observations. To mimic the constraints of limited onboard processing resources, a LEO-PNT module is developed within the new Geoscience Australia's GNSS processing software, Ginan, to process the simulated onboard observations in a Raspberry Pi. The integration of data from higher LEO satellites into the extended Kalman filter model, developed for LEO POD in Ginan, is elucidated and validated through various processing scenarios, including LEO-only case and data fusion with GPS observations. The overall 3D accuracy for the onboard POD is achieved at around 22 cm in the solely LEO-PNT case and improved to about 15 cm with a lower level of observation residuals when combining LEO and GPS observations. This approach holds immense potential for enhancing onboard LEO orbit determination accuracy, robustness, and efficiency.